Strategi Penjadwalan Set Up Mould Dies Mesin Press dengan Menggunakan Metode Overall Equipment Effectiveness (OEE) dan Reliability Centered Maintenance (RCM) - Anwar, Isrizal; Achmadi, Fuad (Program Study Office Adminstrative of Akademi Komunitas Teknologi Syarifuddin Lumajang, 2023)
PT. ABC is a paint manufacturing company that has been established since 1978. The products it produces are various types of paint, both water based and solvent based. Inside PT. ABC has a Metal Production Department whose job is to make paint packaging cans, because PT. ABC makes cans for packaging its paint products independently. One of the work stations that play an important role in the continuity of the production process in the Metal Production Department is the component manufacturing work station. At the work station, the process of making components is carried out using a press machine, namely by carrying out the blanking / punching process on tinplate sheets according to the size needed. Data for 12 months shows maintenance activities that are not optimal and cause high downtime because the machine is damaged, this study aims to find out how much the performance of the machine is using the Equipment Effectiveness (OEE) method as well as the loss of machines that are damaged and reduce very high down time by implementing strategies scheduling of set up intervals on ring sheet press machines with the Reliability Centered Maintenance (RCM) method. The OEE calculation results show an effectiveness value of 77.22%. There are components that are still not good and are below world class standards, namely availability of 79.81% of the standard limit of 90%. And from the results of the six big losses analysis, it is obtained that the losses that are dominant to the low availability value are set up and adjustment with a losses percentage of 10.34%. Factors that affect the high set up and adjustment time are found through fishbone diagrams. RCM analysis is performed to calculate the set up and adjustment time intervals and then make a set up and adjustment time scheduling plan. As well as given suggestions for improvements given through humans, machines, materials, methods, and the environment it is hoped that the effectiveness of the ring sheet press 1 machine can increase.